Comparison Comparison of Isotonic Versus Hypotonic Fluids in Neonates on Maintenance Fluid Therapy - Fatima, Mehak; Gondal, Dr Mudassir Fiaz; Aslam, Hasnain; Rasool, Laraib; Shahwar, Ameena; Ahmed, Waqas (Iranian Journal of Pediatric Surgery, 2025)
Introduction: In neonates, the use of hypotonic fluids is a widely accepted practice to maintain hydration and electrolyte balance, particularly after surgery. However, this approach can increase the risk of hyponatremia due to the lower sodium content in hypotonic solutions compared to blood plasma. This makes neonates more vulnerable to sodium imbalances if not properly monitored. While hypotonic fluids are commonly used, there is growing consideration of isotonic alternatives to reduce the risk of electrolyte disturbances and improve safety in neonatal care. To evaluate and compare the outcomes of using isotonic versus hypotonic fluids in neonates receiving maintenance fluid therapy following surgery. Study place and duration: Department of Pediatric Surgery, Holy Family Hospital, Rawalpindi from January 2023 to December 2023. Material and Methods: Total 84 cases were enrolled in the study who underwent surgery and admitted in neonatal intensive care unit. Infants were randomly divided in two groups. Group I was given isotonic/normal saline with 5% dextrose in 0.9% saline. Group H was given hypotonic saline with 5% dextrose in 0.45% saline. Neonates were followed up and hyponatremia was noted. Data analysis will be done by using SPSS software version 25.0. Results: In Isotonic saline solution, the mean age of neonates was 6.21 ± 6.19 days. In Hypotonic saline solution, the mean age of neonates was 3.84 ± 3.50 days. In Isotonic saline solution, hyponatremia was developed in 2 (4.8%) cases, hypernatremia in 9 (21.4%) cases, while 31 (73.8%) neonates maintained normal serum sodium level. In Hypotonic saline solution, hyponatremia was developed in 11 (26.2%) cases, hypernatremia in 0 (0%) cases, while 31 (73.8%) neonates maintained normal serum sodium level. The difference in both groups was found to be significant (p<0.05). Conclusion: The risk of hyponatremia is higher with hypotonic saline solution when used as maintenance fluid after surgery in pediatric population.